Point of view me, New York City, and the punk scene - Stein, Chris 1950- (Rizzoli, 2018)
"For the duration of the 1970s and onward--from his days as a student at the School of Visual Arts through the foundation of the era-defining band Blondie and his subsequent reign as epicenter of punk's golden age--Chris Stein kept an unrivaled photographic record of the downtown New York City scene. Following in the footsteps of Negative: Me, Blondie, and the Advent of Punk, this spectacular new book presents a more personal and more visceral collection of Chris Stein's photographs of the era. The images presented here take us from self-portraits in his run-down East Village apartment to candid photographs of pop-cultural icons of the time and evocative shots of New York City streetscapes in all their most longed-for romance and dereliction. An eclectic cast of cultural characters--from William Burroughs to Debbie Harry, Andy Warhol to Iggy Pop--appear here exactly as they were in the day, juxtaposed with children playing hopscotch on torn-down blocks, riding the graffiti-ridden subway, or cruising the burgeoning clubs of the Bowery. At once a chronicle of one music icon's life among his punk and New-Wave heroes and peers, and a love letter to the city that was the backdrop and inspiration for those scenes, Point of View transports us to another place and time"--Dust jacket
Keywords: Stein, Chris -- 1950-; New York -- NY, Motiv; Fotografie; Stein, Chris / 1950-; New York (N.Y.) / Pictorial works; New York (N.Y.) / Social life and customs / Pictorial works; Punk rock musicians / Pictorial works; Photography, Artistic; Manners and customs; Punk rock musicians; New York (State) / New York; Pictorial works; Bildband